2021
DOI: 10.3389/fgene.2021.664343
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Detection of Genetic Loci and Candidate Genes for Body Conformation Traits in Duroc × Landrace × Yorkshire Crossbred Pigs

Abstract: The Duroc × (Landrace × Yorkshire) hybrid pigs (DLY) are the most popular commercial pigs, providing consumers with the largest source of pork. In order to gain more insights into the genetic architecture of economically important traits in pigs, we performed a genome-wide association study (GWAS) using the GeneSeek Porcine 50 K SNP Chip to map the genetic markers and genes associated with body conformation traits (BCT) in 311 DLY pigs. The quantitative traits analyzed included body weight (BW), carcass length… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 40 publications
(61 reference statements)
2
17
0
Order By: Relevance
“…With the development of DNA sequencing technology and the reduction in the cost of sequencing and genotyping, whole-genome molecular markers provide powerful tools for studying animal genomes. Tens of thousands of single nucleotide polymorphism (SNP) markers covering the whole pig genome have facilitated the use of molecular breeding strategies such as genomic selection (GS) ( Uemoto et al, 2017 ) and genome-wide association study (GWAS) ( Zhang et al, 2021 ), which has rapidly improved the breeding process of Duroc pigs. In addition, genomic data was utilized to explore selection signatures and reveal potential genetic mechanisms underlying the domestication and evolution of Duroc pigs ( Kim et al, 2015 ; Zhang et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…With the development of DNA sequencing technology and the reduction in the cost of sequencing and genotyping, whole-genome molecular markers provide powerful tools for studying animal genomes. Tens of thousands of single nucleotide polymorphism (SNP) markers covering the whole pig genome have facilitated the use of molecular breeding strategies such as genomic selection (GS) ( Uemoto et al, 2017 ) and genome-wide association study (GWAS) ( Zhang et al, 2021 ), which has rapidly improved the breeding process of Duroc pigs. In addition, genomic data was utilized to explore selection signatures and reveal potential genetic mechanisms underlying the domestication and evolution of Duroc pigs ( Kim et al, 2015 ; Zhang et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Association tests in FarmCPU are validated by FEM with the same computing efficiency as GLM, while the statistical power surpasses that of MLM at the same level of type I errors. In much research, FarmCPU could detect more significant signals than MLM and GLM could in our research [ 4 , 17 , 30 ].…”
Section: Discussionmentioning
confidence: 89%
“…Furthermore, we identified one novel QTL, which was located in a 7.10-Mb region (25.22–32.32 Mb) on SSC7 significantly associated with BL ( Table S7 ). In several previous studies, some significant SNPs associated with BL were also found in the 7.10-Mb region in different pig populations [ 2 , 13 , 16 , 47 ]. Among all SNPs detected, 18 SNPs were located in previously reported QTL regions for growth traits in pigs.…”
Section: Discussionmentioning
confidence: 90%
“…Pork is a popular form of animal protein and is now one of the main sources of human dietary protein. Growth and body size traits, including live backfat thickness (LBT), average daily gain (ADG), body length (BL), body height (BH), back height (BAH), chest circumference (CC), chest depth (CD), and rump circumference (RC), are vital economic traits in the swine industry and have a crucial effect on pig production [ 1 , 2 , 3 ]. Among them, LBT and ADG in different stages are vital indicators of the growth rate of pigs due to their significant impact on production efficiency [ 1 ].…”
Section: Introductionmentioning
confidence: 99%